2000
DOI: 10.1007/pl00002325
|View full text |Cite
|
Sign up to set email alerts
|

Erste Ergebnisse der neoadjuvanten simultanen Radiochemotherapie bei fortgeschrittenen Rektumkarzinomen

Abstract: Preoperative radiochemotherapy followed by surgery is able to achieve clear resection margins in more than 70% of patients with locally advanced rectal cancer and may improve the rate of sphincter-conserving surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…A pCR rate of 8 -10% was found in studies with 5-fluorouracil-based regimens, 5% in an earlier study of our group (Küchenmeister et al, 2000) and the substitution of an oral prodrug for intravenous 5-fluorouracil does not appear to improve these results, with a pCR rate of 4 -9% (Table 4) besides one exception by a group from Korea with a pCR rate of 31% (Kim et al, 2002). Compared with these data, the addition of irinotecan to 5-fluorouracil in the present study resulted in a gross doubling of the pCR rate to over 20%.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…A pCR rate of 8 -10% was found in studies with 5-fluorouracil-based regimens, 5% in an earlier study of our group (Küchenmeister et al, 2000) and the substitution of an oral prodrug for intravenous 5-fluorouracil does not appear to improve these results, with a pCR rate of 4 -9% (Table 4) besides one exception by a group from Korea with a pCR rate of 31% (Kim et al, 2002). Compared with these data, the addition of irinotecan to 5-fluorouracil in the present study resulted in a gross doubling of the pCR rate to over 20%.…”
Section: Discussionmentioning
confidence: 47%
“…Several phase II studies of 5-fluorouracil-based preoperative chemoradiotherapy for locally advanced rectal cancer have reported R0 resection rates of 60 -85% (Chan et al, 1993;Minsky et al, 1993;Keilholz et al, 1995;Videtic et al, 1998;Küchenmeister et al, 2000;Rödel et al, 2000) including pathologic complete response (pCR) rates of 5 -20%. Even in low rectal tumours, sphincter-preserving surgery was possible after preoperative chemoradiotherapy in 27 -86% of the patients (Grann et al, 1997;Hyams et al, 1997;Maghfoor et al, 1997;Küchenmeister et al, 2000). Moreover, randomised trials have shown that neoadjuvant chemoradiotherapy improves local control compared with postoperative chemoradiation in primary resectable tumours (Roh et al, 2001;Sauer et al, 2004).…”
mentioning
confidence: 99%
“…Increase of local control and survival has been shown compared with surgery alone in the Swedish Rectal Cancer Study 1997 [31]. It is widely accepted and supported by excellent phase-II study results that further intensification of preoperative radiotherapy such as addition of several schemes of chemotherapy [14,18] or regional hyperthermia [22] is indicated at least in a highrisk group of patients with locally advanced rectal cancer such as T4 category, distal location and fixation (stage according to Mason). However, for resectable rectal cancer the value of preoperative vs postoperative radiochemotherapy is still under evaluation [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative chemoradiation increases the resection rate (Reerink et al, 2003) and preoperative radiation or chemoradiotherapy decrease local recurrence and reduce small bowel complications compared with postoperative therapy (Minsky et al, 1992;Frykholm et al, 1993, Sauer et al, 2004. R0 resection rates of 60 -85% have reported with 5-FUbased preoperative chemoradiation for LARC (Videtic et al, 1998;Küchenmeister et al, 2000;Rödel et al, 2000).…”
mentioning
confidence: 99%